AIR KELAPA HIJAU MENURUNKAN DISMENORE PADA REMAJA PUTRI - Mariene Wiwin Dolang; Marlen J. Werinusa (Dian Nuswantoro Semarang, 2021)
Menstrual pain or commonly known as dysmenorrhea is muscle cramps felt in the lower abdomen that appear before or during menstruation (menstruation). Menstrual pain is caused by the muscles of the uterine wall contracting, compressing the surrounding blood vessels, as a result, the oxygen supply to the uterus is blocked and triggers pain. The purpose of this study was to determine the effect of giving green coconut water in reducing dysmenorrhoea pain in adolescent girls in the Stikes Dormitory of Pasapua Ambon. This study uses a pre-design experimental design with static group comparison: randomized control group only. The results showed that there was an effect of giving green coconut water to dysmenorrhea in adolescent girls in the Stikes Dormitory of Pasapua Ambon with p = 0.000 (p <0.05). The conclusion is that there is an effect of giving green coconut water on dysmenorrhea in adolescent girls in the STIKES Pasapua Ambon dormitory